Influence of community characteristics on serious police use of force events in an Australian policing jurisdiction: a test of minority threat, social disorganisation, and ecological contamination theories - McCarthy, Molly (Policing and society, 2019)
Extant research on police use of force has established that force is not distributed evenly across communities, with minority threat, ecological contamination, and social disorganisation some of the most common theories used to understand the distribution of police use of force in the US. The current study aimed to test the relevance of these theories for explaining the distribution of serious police use of force events in Australia. We tested a use of force frequency model using negative binomial regression, and a use of force severity model using ordered logistic multilevel modelling. Results demonstrated support for ecological contamination theory, social disorganisation and partial support for socio-economic disadvantage in predicting the frequency of serious police use of force events across communities, while minority threat theory was not supported. In contrast, results suggested that individual and situational factors are more influential in predicting force severity than community characteristics.